The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1038/s41467-021-26018-z
|View full text |Cite
|
Sign up to set email alerts
|

RAB5A expression is a predictive biomarker for trastuzumab emtansine in breast cancer

Abstract: HER2 is a predictive biomarker for HER2-targeted therapeutics. For antibody–drug conjugates (ADCs; e.g., trastuzumab emtansine (T-DM1)), HER2 is utilized as a transport gate for cytotoxic agents into the cell. ADC biomarkers may therefore be more complex, also reflecting the intracellular drug transport. Here we report on a positive correlation between the early endosome marker RAB5A and T-DM1 sensitivity in five HER2-positive cell lines. Correlation between RAB5A expression and T-DM1 sensitivity is confirmed … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 36 publications
(41 reference statements)
2
2
0
Order By: Relevance
“…RAB5A has been recognized as a potential predictive biomarker of response to T-DM1 therapy, and proteins involved in endoplasmic reticulum transport have also been identified as promising predictive biomarkers for ADC treatment strategies, according to scholar Olav Engebraaten, who tested whether clinical response to T-DM1, measured as the pCR, correlates with RAB5A RNA expression, as measured by the I-SPY2 clinical trial (NCT01042379), as a validation experiment. Whether clinical response to T-DM1, as measured by pCR, correlates with RAB5A RNA expression, the study clearly showed a significant correlation between RAB5A expression and breast cancer patients treated with T-DM1 ( p = 0.01, LR test), which was additionally corroborated by the results of the KAMILLA clinical trial (NCT01702571) ( Engebraaten et al, 2021 ; Wolf et al, 2022 ).…”
Section: Discussion and Outlooksupporting
confidence: 58%
“…RAB5A has been recognized as a potential predictive biomarker of response to T-DM1 therapy, and proteins involved in endoplasmic reticulum transport have also been identified as promising predictive biomarkers for ADC treatment strategies, according to scholar Olav Engebraaten, who tested whether clinical response to T-DM1, measured as the pCR, correlates with RAB5A RNA expression, as measured by the I-SPY2 clinical trial (NCT01042379), as a validation experiment. Whether clinical response to T-DM1, as measured by pCR, correlates with RAB5A RNA expression, the study clearly showed a significant correlation between RAB5A expression and breast cancer patients treated with T-DM1 ( p = 0.01, LR test), which was additionally corroborated by the results of the KAMILLA clinical trial (NCT01702571) ( Engebraaten et al, 2021 ; Wolf et al, 2022 ).…”
Section: Discussion and Outlooksupporting
confidence: 58%
“…We demonstrate that αVβ6 integrin co-ordinates HER2 endocytosis, bioavailability and signalling: αVβ6 engagement modulates HER2 phosphorylation and signalling, RAB5 activity and triggers endocytosis of HER2, which then colocalises with RAB5-and RAB7A-positive endosomes. Moreover, this mechanism is perturbed by GDI2 inhibition, which induces constitutive HER2 endocytosis, consistent with a key role for GDI2 in co-ordinating and restricting αVβ6and RAB5-dependent HER2 trafficking (88).…”
Section: Discussionsupporting
confidence: 58%
“…There exists controversy that in patients previously exposed to pertuzumab, the efficacy of T-DM1 could be reduced potentially. Furthermore, the team confirmed that RAB5A protein might be a promising biomarker to predict the sensitivity of T-DM1, which was verified it in selected patients in the KAMILLA study [39].…”
Section: Antibody-drug Conjugatesmentioning
confidence: 67%